How is interreligious sensitivity related to Finnish pupils' religiousness profiles?. Issue 1 (2nd January 2016) - Kuusisto, Elina; Kuusisto, Arniika; Kallioniemi, Arto
Abstract : This paper examines, through a non-probability sample of 451 Finnish lower secondary-school pupils belonging to the 15- to 16-year-old age group, how interreligious sensitivity is related to religiousness profiles of Finnish youth. The data were gathered in two geographical locations: Helsinki, Finland's capital, and a smaller municipality in the western part of Finland. The pupils' self-reported attitudes to interreligious sensitivity were measured using the Interreligious Sensitivity Scale Questionnaire IRRSSQ . The four religiousness profiles identified were strongly religious, culturally religious, personally religious and non-religious. The profiles were related to pupils' interreligious sensitivity. The non-religious group's interreligious sensitivity differed from the other profiles, as these pupils were more in denial and less at the level of acceptance. The results of the study are discussed in the context of the Finnish religious landscape.